Six months follow-up of protected high-risk percutaneous coronary intervention with the microaxial Impella pump: results from the German Impella registry. Issue 3 (May 2020) - Baumann, Stefan; Werner, Nikos; Al-Rashid, Fadi; Schäfer, Andreas; Bauer, Timm; Sotoudeh, Ramin; Bojara, Waldemar; Shamekhi, Jasmin; Sinning, Jan-Malte; Becher, Tobias; Eder, Frederik; Akin, Ibrahim
Abstract : Background: Percutaneous coronary intervention (PCI) represents an important alternative to coronary bypass surgery for the treatment of patients with complex coronary artery disease and high perioperative risk. Protected percutaneous coronary intervention applies temporary percutaneous ventricular assist devices to mitigate potential hemodynamic compromise in high-risk patients. The Impella system is currently the most commonly used device for protected percutaneous coronary intervention and showed improved hemodynamic parameters in earlier trials. Methods: This study was designed as a retrospective, observational multi-center registry conducted in ten hospitals in Germany. We included consecutive patients undergoing protected high-risk percutaneous coronary intervention with Impella support. The primary endpoint was defined as the occurrence of a major adverse cardiac event defined as all-cause mortality, ST-elevation myocardial infarction, or stroke during a postprocedural 180-day follow-up period. Results: In total, 157 patients (80.3% male; mean age 71.8 ± 10.8 years) were included in the present study, and 180-day follow-up was complete for 149 patients (94.9%). At baseline, the patients had a median left ventricular ejection fraction of 39.0% (interquartile range, 25.0–50.0%). The median SYNergy between PCI with TAXUS and Cardiac Surgery-Score I was 33.0 (interquartile range, 24.0–40.5) and the median EuroSCORE II was 7.2% (interquartile range, 3.2-17.1%). During postprocedural follow-up, 34 patients (22.8%) suffered a major adverse cardiac event. All-cause mortality was 18.1% (27 patients). Nine patients (6.0%) sustained a ST-elevation myocardial infarction, while 4 patients (2.7%) had a stroke. Conclusions: Patients undergoing protected high-risk percutaneous coronary intervention with Impella support showed an acceptable 180-day clinical outcome regarding major adverse cardiac event and mortality.